Numerical and experimental study of tunneled raft foundation (Nexo Revista Científica, 2023)
Models are created, inspected in the experimental research, and compared to the numerical study in the PLAXIS 3D.V20 program in order to stay up with the advancement of studies in the area of geotechnical engineering. The purpose of the model is to investigate how existing tunnels affect shallow foundations. a simulation of reality a tunnel with specifications [Elastic modulus = 70 Gpa, Poisson's ratio = 0.33] with three locations for the tunnel 15, 30, 45 cm measured from the bottom of the foundation), an iron box with dimensions (80*80*60 cm), and a foundation with dimensions (20*20 cm). It was discovered that the tunnel's position significantly affects the soil's ability to support additional loads, and that the effect diminishes as the distance between the foundation and the tunnel grows. The tunnel's depth (15 cm) increased by the most—105.9%—followed by its depth (30 cm), which increased by 21.5%, and its depth (45 cm), which increased by 3.9%.